Impact of COVID-19 on care-home mortality and life expectancy in Scotland. (29th April 2021) - Burton, Jennifer K; Reid, Martin; Gribben, Ciara; Caldwell, David; Clark, David N; Hanlon, Peter; Quinn, Terence J; Fischbacher, Colin; Knight, Peter; Guthrie, Bruce; McAllister, David A
Abstract: Background: COVID-19 deaths are commoner among care-home residents, but the mortality burden has not been quantified. Methods: Care-home residency was identified via a national primary care registration database linked to mortality data. Life expectancy was estimated using Makeham–Gompertz models to (i) describe yearly life expectancy from November 2015 to October 2020 (ii) compare life expectancy (during 2016–18) between care-home residents and the wider population and (iii) apply care-home life expectancy estimates to COVID-19 death counts to estimate years of life lost (YLL). Results: Among care-home residents, life expectancy in 2015/16 to 2019/20 ranged from 2.7 to 2.3 years for women and 2.3 to 1.8 years for men. Age–sex-specific life expectancy in 2016–18 in care-home residents was lower than in the Scottish population (10 and 2.5 years in those aged 70 and 90, respectively). Applying care home-specific life expectancies to COVID-19 deaths yield mean YLLs for care-home residents of 2.6 and 2.2 for women and men, respectively. In total YLL care-home residents have lost 3, 560 years in women and 2, 046 years in men. Approximately half of deaths and a quarter of YLL attributed to COVID-19 were accounted for by the 5% of over-70s who were care-home residents. Conclusion: COVID-19 infection has led to the loss of substantial years of life in care-home residents aged 70 years and over in Scotland. Prioritising the 5% of older adults who are care-home residents for vaccination is justified not only in terms of total deaths, but also in terms of YLL.